PENGARUH VARIASI ARUS LISTRIK DAN KECEPATAN PENGELASAN PADA ELEKTRODA RB-26 TERHADAP KEKERASAN LOGAM LAS DAN HAZ BAJA ST-37 - Muh Ahar (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Welding is an important part of industrial growth, as it plays an important role in construction. Most modern industries always involve welding processes which are increasing every year. Many errors occur in the selection of the amount of electric current and welding speed which affects the weld area and HAZ area. This study aims to determine the level of hardness from the effect of variations in electric current and welding speed on weld metal and HAZ. This research uses experimental methods and is also supported by the Shielded Metal Arc Welding (SMAW) welding method, as well as the rockwell hardness test method HRD-150 model. The number of specimens in this welding is 10 pieces, consisting of 1 raw material and 9 welding specimens. The number of samples in this rockwell hardness test for each variation of electric current and speed is 9 samples.For the raw material tested, the hardness value obtained is 51.5 HRB. In specimen testing, the highest hardness value is obtained at an electric current of 70 A with an average hardness of 52.75 HRB while the lowest hardness value is at an electric current of 90 A with a value of 50.72 HRB. Tests carried out on the heat affected area or Heat Affected Zone (HAZ), the highest hardness value at an electric current of 90 A with a hardness number of 52.6 HRB and the lowest hardness value at an electric current of 70 A with a hardness number of 50.97 HRB. This research result means that the high and low strength of electric current and speed at the time of welding affects the hardness value of the carbon steel plate equivalent to St 37 which has been welded with different currents as a whole due to heat input during welding.